The Network Nullspace Property for Compressed Sensing of Big Data Over Networks - Jung, Alexander; Hulsebos, Madelon (Frontiers in Applied Mathematics and Statistics, 2018)
We present a novel condition, which we term the net- work nullspace property, which ensures accurate recovery of graph signals representing massive network-structured datasets from few signal values. The network nullspace property couples the cluster structure of the underlying network-structure with the geometry of the sampling set. Our results can be used to design efficient sampling strategies based on the network topology.